Effects of Ischemic Acute Kidney Injury on Lung Water Balance: Nephrogenic Pulmonary Edema? - Rajit K. Basu; Derek Wheeler (Pulmonary Medicine)
Pulmonary edema worsens the morbidity and increases the mortality of critically ill patients. Mechanistically, edema formation in the lung is a result of net flow across the alveolar capillary membrane, dependent on the relationship of hydrostatic and oncotic pressures. Traditionally, the contribution of acute kidney injury (AKI) to the formation of pulmonary edema has been attributed to bulk fluid accumulation, increasing capillary hydrostatic pressure and the gradient favoring net flow into the alveolar spaces. Recent research has revealed more subtle, and distant, effects of AKI. In this review we discuss the concept of nephrogenic pulmonary edema. Pro-inflammatory gene upregulation, chemokine over-expression, altered biochemical channel function, and apoptotic dysregulation manifest in the lung are now understood as “extra-renal” and pulmonary effects of AKI. AKI should be counted as a disease process that alters the endothelial integrity of the alveolar capillary barrier and has the potential to overpower the ability of the lung to regulate fluid balance. Nephrogenic pulmonary edema, therefore, is the net effect of fluid accumulation in the lung as a result of both the macroscopic and microscopic effects of AKI.